LEGAL AWARENESS OF HOUSEHOLD DISPUTE RESOLUTION THROUGH NONLITIGATION IN MALALO - Putra, Mulyadi; Atsani, Ulya; Warman, Arifki Budia (Institut Agama Islam Negeri Batusangkar, 2024)
This research aims to analyze legal awareness regarding the resolution of household disputes through non-litigation in Jorong Rumbai Nagari Padang Laweh Malalo. This type of research is sociological juridical with a qualitative typology. The results of this research are, first, forms of resolving household disputes through non-litigation with consensus deliberation. Second, there is a lack of public awareness regarding the existence of regulations for non-litigation resolution of household disputes. Third, the impact of resolving household disputes through non-litigation on household conditions is the establishment of household harmony. From all of this it can be concluded that some people do not have legal awareness in resolving disputes through non-litigation, even though the impact of non-litigation resolution can resolve problems well.